Novel CDRC-TLM algorithm for the analysis of magnetized plasma - Adraoui, Soufiane El; Khalid, Mounirh; Zugari, Asmaa; Yaich, Mohamed Iben; Khalladi, Mohsine (Optik (Stuttgart), 2014)
This paper presents a novel approach to model the interaction of electromagnetic waves with the magnetized plasma medium based on the Transmission Line Matrix (TLM) method. Anisotropic and dispersive characters of magnetized plasma are modeled by voltage sources, where the formulation is developed using the Current Density Recursive Convolution (CDRC) technique. Computational examples illustrate not only the improved accuracy, but also significant CPU time saving in comparison with TLM Constant Recursive Convolution (CRC-TLM) approach.